2014
DOI: 10.1513/annalsats.201403-094oc
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Socioeconomic Status–related Differences in Mortality among People with Chronic Obstructive Pulmonary Disease

Abstract: Mortality in people with COPD has decreased faster in people with the highest compared with the lowest SES, causing increased disparity between rich and poor. Further study and strategies are needed to explore and address factors responsible for this increasing disparity in the COPD population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 20 publications
1
32
0
3
Order By: Relevance
“…In a study by Gershon et al [28], based purely on household income in a single payer healthcare system, it was found that there was statistically significant difference in the mortality difference between the lowest and highest income quintiles. Mortality increased from 67 per 10,000 individuals in 1996-1997 to 86 per 10,000 individuals representing a 28% relative increase.…”
Section: Chronic Obstructive Pulmonary Disease (Copd)mentioning
confidence: 99%
See 1 more Smart Citation
“…In a study by Gershon et al [28], based purely on household income in a single payer healthcare system, it was found that there was statistically significant difference in the mortality difference between the lowest and highest income quintiles. Mortality increased from 67 per 10,000 individuals in 1996-1997 to 86 per 10,000 individuals representing a 28% relative increase.…”
Section: Chronic Obstructive Pulmonary Disease (Copd)mentioning
confidence: 99%
“…It was also observed that mortality in people with COPD has decreased faster in people with the highest compared with the lowest SES, causing increased disparity between rich and poor. Further study and strategies are needed to explore and address factors responsible for this increasing disparity in the COPD population [28]. Lewis et al [25] analyzed traditional markers of SES as well as other contextual measures and determined that a lower household income and educational status were independent risk factors for mortality due to COPD.…”
Section: Chronic Obstructive Pulmonary Disease (Copd)mentioning
confidence: 99%
“…[2] Even in high-income countries, there is a definite trend in socioeconomic related outcome with those in the lower socioeconomic status faring worse. [3] The high economic burden this disease imposes on the individual, and the health care delivery system of a nation needs to be emphasized. [4]…”
Section: Introductionmentioning
confidence: 99%
“…A low SES affects not only the risk of developing COPD but is linked to poorer outcomes. It has been associated with decreased lung function and performance, lower rates of medication use, higher rates of hospitalization, and increased mortality [4-7]. COPD patients with a low SES may also have a lower degree of health literacy; i.e., the ability to obtain, process, and understand basic health-related information, which is needed to make appropriate healthcare decisions [8].…”
Section: Change Your View On Patientsmentioning
confidence: 99%